(untitled) (Nepal Medical College Journal, 2025)
Our daily activities to professional handicrafts require the use of fingertips one way or other and such important anatomical parts are prone to significant injuries either at home or at work. The injuries if not managed properly can lead to devastating consequences with significant disability. The aim of this study was to identify the incidence of such injuries and the causes behind them along with the treatment options. A retrospective, hospital based study evaluating fingertip injuries at Nepal Medical College Teaching Hospital was conducted from April of 2023 to September 2024. Patients with fingertip injuries presenting to outpatient departments and emergencies were enrolled in this study. Total of 117 patients were enrolled with mean age of 27.37 years and 81.2% were males. Most of the injuries had occurred at workplace (64.1%) and most common mode of injury was cut injury (74.1%). Long finger was most commonly injured finger (25.6%) followed closely by index finger (23.9%) and thumb (16.2%). Allens type 2 was the most common grade of injury (78.6%). Primary repair was successfully performed in most of the patients (82.9%). Some patients required thenar flap (8.5%), V-Y flap (3.4%), cross finger flap (1.7%), FDMA flap (0.9%) and amputation (2.6%). Cut injuries were the most common mode of injury primarily affecting adult males in industrial settings so workplace safety protocols should be implemented to reduce the incidence of these injuries. Different patients and different grades of injuries require different approaches so as to approach each case uniquely.